Estrategias metodológicas y su incidencia en el aprendizaje del área de ciencias sociales de los estudiantes del décimo año de educación básica de la unidad educativa “Los Guayacanes”, cantón Quevedo, periodo 2021-2022 - Zúñiga Sánchez, Beatriz Del Rocio (2022)
The methodological strategies are relevant in the educational field and must be addressed to the learning needs of the students in order to motivate and significantly improve the learning process. The main objective of this research is to analyze the methodological strategies and their impact on learning in the area of social sciences to innovate in the learning of students in the tenth year of basic education of the "Los Guayacanes" Educational Unit, and in this way know the current situation, to propose a solution proposal through training in improving educational praxis and the learning process of students. The methodology applicable in the investigative work has a type of field investigation due to its realization within the institution, exploratory by the applied survey, descriptive allowed to analyze the variables and quantitative applied in the quantifiable collection of information, for which used as a research instrument the survey applied to the population of 240 students in the tenth year of basic education and 12 teachers in the social area. The results of the research allow the application of the proposal to implement training for teachers regarding innovative methodological strategies in order to improve educational practice and the learning process of students. Finally, it is recommended to give continuity to this type of training and apply it to the different areas of the institution